2001
DOI: 10.1897/1551-5028(2001)020<1680:earaol>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Risk Assessment of Linear Alkylbenzene Sulfonates in Agricultural Soil. 4. The Influence of Salt Speciation, Soil Type, and Sewage Sludge on Toxicity Using the Collembolan Folsomia Fimetaria and the Earthworm Aporrectodea Caliginosa as Test Organisms

Abstract: Sewage sludge applied to agricultural soils often contains linear alkylbenzene sulfonates (LAS) in the range of 1 to 10 g/kg dry weight, and their toxicity to relevant soil organisms should, therefore, be assessed to ensure safe use of sewage sludge as a fertilizer. Studies of LAS toxicity to soil organisms are few, and to our knowledge, factors that may influence the toxicity in the field have not been studied in detail. In this paper, we report on the influence of speciation of LAS in the test solution added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…The effects of LAS on the reproduction of F. candida [6] were possibly due to an enhanced mobilization of toxic compounds in the sludge, because surfactants may increase the availability of sorbed organic chemicals [26]. Holmstrup et al [27] found that increasing periods of anaerobic incubation of sludge with added LAS increased the toxicity of LAS to earthworms and Collembola. These authors concluded that LAS might have mobilized other toxic compounds in the sludge.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of LAS on the reproduction of F. candida [6] were possibly due to an enhanced mobilization of toxic compounds in the sludge, because surfactants may increase the availability of sorbed organic chemicals [26]. Holmstrup et al [27] found that increasing periods of anaerobic incubation of sludge with added LAS increased the toxicity of LAS to earthworms and Collembola. These authors concluded that LAS might have mobilized other toxic compounds in the sludge.…”
Section: Discussionmentioning
confidence: 99%
“…Soil from the plough layer was sampled at an agricultural field (Lundgaard, Denmark) in August 1997. The soil was a coarse sand (coarse sand, 67%; fine sand, 16%; silt, 8.6%; clay, 6.2%; humus, 2.7%) with a total C content of 1.5% [11]. This soil type represents approximately 25% of the cultivated area in Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…It is a sandy loam soil with a pH of 5.8, total organic carbon 1.36%, clay 11.6%, silt 21.4%, and sand 64.7%. Further information is available in Holmstrup et al (2001). Prior to the experiment the soil was oven-dried (Memmert, Type UL40) at 80°C for 24 h to eliminate undesired soil fauna.…”
Section: Test Species and Test Soilmentioning
confidence: 99%